Pengaruh Pemberian Pekerjaan Rumah dan Bimbingan Orang Tua Terhadap Kedisiplinan Belajar Siswa di SD Negeri Cermo III Sambi Tahun 2015/2016 - Wulandari, Septina Dwi (2016)
This study aimed to determine the effect of homework and guidance of parents to discipline the student's learning in elementary school Cermo III Sambi year 2015/2016. The sample population studied were all students in upper classes (IV, V, VI) SDN Cermo III. Collecting data in this study using the technique of questionnaires, interviews and documentation as a source of research. To test instrument to test the validity and reliability testing. Then do the analysis prerequisite test covering normality test and reliability test. Data analysis technique of this study is to test the linear, hypothesis testing using t test and F test Based on the calculation hypothesis test or t test obtained thitung X1> ttable namely 2.432> 2.017 and thitung X2> ttable namely 2.666> 2.017. In the F test obtained Fhitung> Ftable is 11.656> 3.23. Thus, from this study it can be concluded that there are significant and guidance homework is oran parents to discipline the student's learning in primary school Cermo III. Effective Relative donations and donations in giving homework SR = SE = 46.73% and 16.68%. On parental guidance for SR = SE = 53.18% and 18.98%. It can be concluded that the guidance of the parents has a greater influence on the discipline of learning than homework. Keywords: homework,learning discipline, parental guidance.